Inequalities in health outcomes of SARS-CoV-2 infection by migration status in Barcelona, Spain - Pérez-Muto, Valeria; Bertran, Maria Jesús; Barón-Miras, Lourdes; Torá-Rocamora, Isabel; Gualda-Gea, Juan José; Vilella, Anna (Frontiers in Public Health, 2024)
Background: Migrants are a vulnerable population at risk of worse health outcomes due to legal status, language barriers, and socioeconomic and cultural factors. Considering the conflicting literature on the subject, it is important to further explore the extent and nature of these inequalities. Objective: The aim of this study is to compare health outcomes associated with SARS-CoV-2 infection between Spanish native and migrant population living in Barcelona. Methods: Observational retrospective cohort study including all adult cases of SARS-CoV-2 infection who visited a tertiary hospital in Barcelona between the 1st March 2020 and the 31st March 2022. We established the following five health outcomes: the presence of symptomatology, hospitalisation, intensive care unit admission, use of mechanical ventilation, and in-hospital 30day mortality (IHM). Using Spanish natives as a reference, Odds Ratios (OR) with 95% CI were calculated for migrants by multivariate logistic regression and adjusted by sociodemographic and clinical factors. Results: Of 11,589 patients (46.8% females), 3,914 were born outside of Spain, although 34.8% of them had legal citizenship. Most migrants were born in the Americas Region (20.3%), followed by other countries in Europe (17.2%). Migrants were younger than natives (median 43 years vs 65 [49-78] years) and had a higher socioeconomic privation index, less comorbidities, and fewer vaccine doses. Adjusted models showed migrants were more likely to report SARS-CoV-2 symptomatology with an adjusted OR of 1.36 (95%CI 1.20-1.54), and more likely to be hospitalised (OR 1.11 [IC95% 1.00-1.23], p=0.043), but less likely to experience IHM (OR 0.67 [IC95% 0.47-0.93], p=0.02). Conclusion: Characteristics of migrant and native population differ greatly, which could be translated into different needs and health priorities. Native population had higher odds of IHM, but migrants were more likely to present to care symptomatic and to be hospitalised. This could suggest disparities in healthcare access for migrant population. More research on health disparities beyond SARS-CoV-2 in migrant populations is necessary to identify gaps in healthcare access and health literacy.